An ontological and enactive tool for education in management of coexistence - García de la Cerda, Osvaldo (2016)
Higher Education and the management of coexistence is an issue that is beginning to be included in the training of students and in teaching based on the demands made to teachers by the civil society and by the State in the last decade. The Ministry of Education of Chile formulates a National School Coexistence Policy that is being applied since 2002 in the country’s schools. It provides a conceptual and ethical framework to understand and act school coexistence from a rights and gender approach. It requires schools and universities to deal actively with this issue by placing teachers and professors as Promotors of Coexistence, i.e., it stresses their responsibility (beyond the disciplinary setting) in creating the conditions for training in citizenship, personal and social ethics, socio-emotional development, and social skills, among others. This obligation requires the teachers to question how they are acting, in their own coexistence and rupture spaces, to incorporate distinctions that allow them to act in the future from a pedagogical and generative perspective as established by the new State demands.